Vivenciando a sobrecarga ao vir-a-ser um cuidador familiar de pessoa com acidente vascular cerebral (AVC): análise do conhecimento. - Bocchi, Silvia Cristina Mangini (My University, 2004)
This bibliographical research aims to carry out a thematic analysis of knowledge production in periodicals, about the burden placed on family caregivers of Cerebrovascular Accident (CVA) survivors. The analysis gathered articles found in the 80 and 90, through the Medline, Lilacs and Cinahl databases. The content analysis was the methodological background that enabled us to organize the whole knowledge into a body of categories and subcategories, called: Category 1 - The sequels of the CVA creating burden, Category 2 - Aspects generating burden, covering the following subcategories: social isolation, marital changes and dissatisfactions, family caregivers' financial difficulties and deficits in their physical health and self-care, Category 3 - Other analyses about burden in CVA survivorś family caregivers.
Living the burden in becoming a family caregiver for a cerebrovascular accident survivor: knowledge analysis